Erythropoietin produced by genetic-modified NIH/3T3 fibroblasts enhances the survival of degenerating neurons - Li, Yi-Chin (Brain Behav, 2015)
BACKGROUND: Erythropoietin (EPO) has potent neuroprotective effects. The short-term delivery of high-dose EPO seemed to improve patients’ neuromuscular functions; however, excessive EPO resulted in systematically high hematocrit and thrombotic risk. In our study, we established a cellular material for future in vivo studies of neurodegenerative diseases based on EPO provided regionally at a nontoxic level. METHODS: A mouse EPO cDNA was subcloned into the pCMS-EGFP vector and transfected into NIH/3T3 fibroblasts to design a biological provider that can regionally release EPO for the treatment of neurological diseases. After G418 selection, a stable EPO-overexpressing cell line, EPO-3T3-EGFP, was established. To further confirm the neuroprotective abilities of secreted EPO from EPO-3T3-EGFP cells, a cell model of neurodegeneration, PC12-INT-EGFP, was applied. RESULTS: The expression level of EPO was highly elevated in EPO-3T3-EGFP cells, and an abundant amount of EPO secreted from EPO-3T3-EGFP cells was detected in the extracellular milieu. After supplementation with conditioned medium prepared from EPO-3T3-EGFP cells, the survival rate of PC12-INT-EGFP cells was significantly enhanced. Surprisingly, a fraction of aggregated cytoskeletal EGFP-tagged α-internexin in PC12-INT-EGFP cells was disaggregated and transported into neurites dynamically. The immunocytochemical distribution of IF proteins, including NF-M, phosphorylated-NF-M, and the α-INT-EGFP fusion protein, were less aggregated in the perikaryal region and transported into neurites after the EPO treatment. CONCLUSION: The established EPO-overexpressing NIH/3T3 cell line, EPO-3T3-EGFP, may provide a material for future studies of cell-based therapies for neurodegenerative diseases via the secretion of EPO on a short-term, high-dose, regional basis.